Solid state switching using wireless network in home automation. (2021) - Karpagam, R.; Sathishkumar, G.K.; Megala, V.; Lydia, J.; Priya, N.; Abhishek Dheeven, T.
Abstract: The globe is presently perusing technologies that entirely automate the processes with negligible losses. To achieve this, the world has initiated their automation from private bodies like home, school, etc. Thus, our paper is created to aid their process. This paper describes the solid-state switching using wireless networks. The proposed paper deals with the replacement of solid-state device instead of application of relays in home automation, as the performance of relays are not very effective in switching at higher inrush currents and they require an adequate environment for its better performance. Solid state devices have advantages like less power consumption, better life span, easy control, etc. Thus, the use of solid-state devices improves the performance of the entire home automation system. This proposed paper uses a protocol DALI (Digitally Addressable Lighting Interface) which controls switching of light resistive loads and improves communication. The soft switching operation of the circuit operates with the wireless network and improves the ability of carrying loads and has a strong controlling ability. The design and circuit framework can be adapted to any of the switch-controlled circuits which is relayed on solid state device.